2019
DOI: 10.18632/aging.102156
|View full text |Cite
|
Sign up to set email alerts
|

LINC00511 promotes the malignant phenotype of clear cell renal cell carcinoma by sponging microRNA-625 and thereby increasing cyclin D1 expression

Abstract: The expression pattern and detailed roles of long noncoding RNA LINC00511 in clear cell renal cell carcinoma (ccRCC) remain unknown. We measured LINC00511 expression in ccRCC. We clarified the clinical characteristics associated with LINC00511 in ccRCC. We examined the biological roles of LINC00511 in the progression of ccRCC, and we identified the potential mechanisms involved. LINC00511 was upregulated in ccRCC tissues and cell lines. High LINC00511 expression significantly correlated with TNM classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Next, these 73 studies were carefully screened by the titles, abstracts, and full texts. Finally, a total of 13 eligible studies comprising 1053 cancer patients were included according to the inclusion and exclusion criteria in this meta-analysis [ 9 , 10 , 16 , 17 , 21 , 22 , 25 , 28 , 33 35 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, these 73 studies were carefully screened by the titles, abstracts, and full texts. Finally, a total of 13 eligible studies comprising 1053 cancer patients were included according to the inclusion and exclusion criteria in this meta-analysis [ 9 , 10 , 16 , 17 , 21 , 22 , 25 , 28 , 33 35 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] In thyroid cancer, Chen et al [ 37 ] revealed that LINC00511 could bind to TATA-box binding protein-associated factor 1 to activate Janus kinase 2/signal transducer and activator of transcription 3 signaling pathway, which remarkably decreased the radio-sensitivity of malignant cells. In renal cell cancer cells, Deng et al [ 25 ] found that LINC00511 was capable of promoting the proliferation, colony formation, in vitro invasion, and in vivo tumor growth, as well as inhibit apoptosis of cancer cells, by repressing the miR-625 and consequently upregulating CCND1. [ 25 ] Collectively, these studies provide extensive evidences that LINC00511 may act as an oncogene in human malignancies, which strongly supported the findings of our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LINC00511 is an oncogene which plays a negative regulatory role in cell proliferation, cell cycle progression, apoptosis, invasion, migration, metastasis and chemoresistance [15][16][17][18][19][20][21][22][23]. Noteworthily, overexpression of LINC00511 was shown to be a predictor for cancer prognosis [16,18,20,22,[24][25][26][27][28]. However, the results of the studies were not consistent.…”
Section: Introductionmentioning
confidence: 99%